Experiences of patients with cancer at health care facilities in Japan: results from a nationwide survey - Tomone Watanabe; Yuichi Ichinose; Mei Matsuki; Takafumi Wakita; Tsutomu Toida; Masato Masuda; Takahiro Higashi (BMC, 2021)
Abstract Background To elucidate the experience of patients with cancer from diagnosis to early survivorship in Japan using a nationwide questionnaire survey, and to inform the current progress of the cancer control programs. Methods The survey was sent to a representative sample of adult patients with cancer identified from the national database of hospital-based cancer registries. The patients' responses were compared across three groups: patients with rare cancers, patients aged < 40 years, and patients with non-rare cancers aged ≥40 years. Results Of 20,488 patients invited to participate in the survey, 8935 (43.6%) responded. Respondents reported an average score of 7.9 out of 10 on global ratings of care. Patients with rare cancers experienced a longer time to diagnosis but the shortest time from diagnosis to first treatment (p < 0.05). Patients aged < 40 years rated worse for the majority of the survey items, especially on items that related to communication with medical staff and items referring to early survivorship. Conclusion The care experienced by patients with cancer in Japan varies on the basis of age group and cancer type. Efforts should be directed to ensuring prompt access to diagnostic facilities for patients with rare cancers and providing sufficient support to younger patients.